In vivo evidence for GABA A receptor changes in the sensorimotor system in primary dystonia - Garibotto, Valentina; Romito, Luigi M.; Elia, Antonio E.; Soliveri, Paola; Panzacchi, Andrea; Carpinelli, Assunta; Tinazzi, Michele; Albanese, Alberto; Perani, Daniela (Movement disorders, 2011)
Preclinical and clinical evidence suggests that impaired gamma-aminobutyric (GABA) control, leading to disinhibition within the sensorimotor system, might play a role in dystonia. Aim of this study is the in vivo assessment of the GABAergic system in dystonia using positron emission tomography (PET) and (11) C-flumazenil, a selective GABA(A) receptor ligand. Fourteen subjects with primary dystonia (9 carriers of the DYT1 mutation and 5 sporadic cases) were compared to 11 controls, using a simplified reference tissue model to measure binding potential. Voxel-based analyses showed a reduction in GABA(A) receptor expression/affinity both in DYT1 carriers and sporadic patients in primary motor and premotor cortex, primary and secondary somatosensory cortex, and in the motor component of the cingulate gyrus. Dysfunction of GABA(A) receptors in sensorimotor systems in primary (genetic and sporadic) dystonia supports the view that lack of GABAergic control may be associated with the generation of dystonic movements.